Majorbio Cloud: A one‐stop, comprehensive bioinformatic platform for multiomics analyses. Issue 2 (16th March 2022) - Ren, Yi; Yu, Guo; Shi, Caiping; Liu, Linmeng; Guo, Quan; Han, Chang; Zhang, Dan; Zhang, Lei; Liu, Binxu; Gao, Hao; Zeng, Jing; Zhou, Yong; et al.
Abstract : The platform consists of three modules, which are pre‐configured bioinformatic pipelines, cloud toolsets, and online omics' courses. The pre‐configured bioinformatic pipelines not only combine analytic tools for metagenomics, genomes, transcriptome, proteomics and metabolomics, but also provide users with powerful and convenient interactive analysis reports, which allow them to analyze and mine data independently. As a useful supplement to the bioinformatics pipelines, a wide range of cloud toolsets can further meet the needs of users for daily biological data processing, statistics, and visualization. The rich online courses of multi‐omics also provide a state‐of‐art platform to researchers in interactive communication and knowledge sharing.